The journeys of current West African crops - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Foods of West Africa. Their Origin and Use I F Smith. 1998. 262 pp. ISBN 0 9684255 0 x US$30 (e27.80) (excl. postage) 16 Rhapsody Lane, Ottawa, Ontario, Canada K1V 1B1. Fax: +1 613 247 0578 Email: nosi.smith@sympatico.ca